Учет влияния на скрытность wi-fi каналов связи их электродинамических характеристик и условий распространения радиоволн - Стрельницкий, А. А.; Шокало, В. М.; Ягудина, Е. В.; Абдул-Хуссейн, М. К. (ХНУРЭ, 2011)
The safety of Wi-Fi channels is usually characterize by the probability of detection Роб, which depends on wave propagation (WP). The article sets out options for models of WP, which take into account the peculiarities of the Wi-Fi radio. These models are then used for numerical analysis of the safety of a local wireless radio link according to the criterion Роб0,7. A relation connecting the probability to detected the operation of wireless digital communication systems (DCS) depending on the size of the aperture and diverting legitimate channels and their mutual arrangement has been obtained. It has been displayed, that the main factors affecting the efficiency of detection is removal of the legitimate and side channel receiving aperture from the aperture of the emitters and scatterers source of information, as well as the value of the secret speed.
Keywords: Wi-Fi технологии; конфиденциальная связь